Adapting to, integrating and self-managing HIV as a chronic illness: a scoping review protocol - Edwin Wouters; Lucia Knight; Caroline Masquillier; Neo Phyllis Sematlane (BMJ Open)
Introduction The process of adapting to a life with a chronic illness, is a well-researched phenomenon for a number of common chronic illnesses. The construct, adaptation, embeds the notions of integration of the chronic illness into identity and self-management. Integration precedes self-management and is key to living positively with a chronic illness. Adaptation is an important concept in understanding trajectory and outcomes of living with a chronic illness. Applicability of these concepts to HIV as a chronic illness; when suppressive adherence has been achieved, however, is unknown. Specifically, the adaptation process to living with HIV as a chronic illness, the integration of HIV into identity and the resulting self-management behaviours by adults living with HIV are relatively unexplored. We describe a protocol for a scoping review of adaptation to living with HIV, we structure the enquiry around integration of HIV into identity and self-management and interrogate theories, models and frameworks that have been proposed and studied and we evaluate them for relevance and usefulness in the care and management of HIV.Methods and analysis Methods proposed by the Johanna Briggs Institute will be followed. The protocol was drafted using the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for Scoping Reviews and was registered with the Open Science Framework. MEDLINE, SCOPUS, Cochrane Library, CINHAL and SocINDEX databases will be searched. A search in Social Science Research Network eLibrary and Open Access Theses and Dissertations will gather grey literature and reference lists of included sources will be screened. Study selection process will involve a title and abstract review and full text review, guided by clearly defined inclusion and exclusion criteria.Ethics and dissemination Ethical approval is not required because this is a proposed review and collection of data on publicly available materials. The results will be published in a topic relevant journal and presented at related scientific events.